2016
DOI: 10.3390/ijerph14010025
|View full text |Cite
|
Sign up to set email alerts
|

Gendered Sources of Distress and Resilience among Afghan Refugees in Northern California: A Cross-Sectional Study

Abstract: Recent studies have emphasized the influence of resettlement factors on the mental health of refugees resettling in developed countries. However, little research has addressed gender differences in the nature and influence of resettlement stressors and sources of resilience. We address this gap in knowledge by investigating how gender moderates and mediates the influence of several sources of distress and resilience among 259 Afghan refugees residing in Northern California (USA). Gender moderated the effects o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…We also find SAT's conceptions of 'dissonant acculturation' helpful but too confining for thinking clearly about the complex patterns of identification and distinction among Afghan Americans. Stempel et al (2016) have shown how consequential dissonant acculturation, especially around gender roles, is for the well-being of Afghan refugees in northern California. We expect that a robust understanding of Afghan boundary work and responses to stigmatisation will illuminate the identities and strategies influenced by patterns of dissonant and consonant acculturation.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…We also find SAT's conceptions of 'dissonant acculturation' helpful but too confining for thinking clearly about the complex patterns of identification and distinction among Afghan Americans. Stempel et al (2016) have shown how consequential dissonant acculturation, especially around gender roles, is for the well-being of Afghan refugees in northern California. We expect that a robust understanding of Afghan boundary work and responses to stigmatisation will illuminate the identities and strategies influenced by patterns of dissonant and consonant acculturation.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Much existing work on Afghans in the U.S., including our own, has been based on small community surveys or qualitative studies focused on the health and mental health effects of pre-migration war traumas and post-migration stressors (Alemi et al 2014;Stempel et al 2016). Although previous work has sensitised us to a variety of issues and challenges U.S. Afghans face that may affect their economic integration, we are aware of no prior research on Afghan American economic conditions or integration.…”
Section: Introductionmentioning
confidence: 99%
“…According to Beiser, Simich, Pandalangat, Nowakowski, and Tian (2011), strong ethnic identity provides further psychological advantage. Intimate and extended family ties have little correlation with men’s distress levels, but are strongly associated with lower distress for women (Stempel et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The consideration of a wide range of topics is needed to better inform decision makers and the medical community [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. This includes, but is not limited to: Health screening examinations; community-based/multi-lingual health education and resources for refugees; improved awareness of refugee health disparities; disease tracking and reporting systems; multidisciplinary response to disease outbreaks; refugee utilization or lack thereof of healthcare resources/insurance; barriers to healthcare; health selection/trajectory of refugees; hematologic genetic disorders; chronic and mental health issues; abuse; discrimination; exploitation; infectious diseases; immunization strategies; environmental exposures related to disease; hygiene and sanitation; healthy lifestyle choices; illegal activities/injuries (assault, rape, battery); and assimilation analysis.…”
Section: Moving Toward a Solutionmentioning
confidence: 99%